Patent ductus arterious and increased conjugated bilirubin in the second week after birth are independent risk factors for necrotizing enterocolitis in preterm infants: an observational study - Xiaoya Han; Shudong Cui (BMC, 2023)
Abstract Background Neonatal necrotizing enterocolitis (NEC) is a common critical illness of the gastrointestinal system in neonatal intensive care units with complex causes. We want to explore effects of serum-conjugated bilirubin on the occurrence of NEC in preterm infants. Methods A retrospective study of clinical case data of premature infants from 2017 to 2020 in the Department of pediatrics of the First Affiliated Hospital of Nanjing Medical University was conducted. Among these, 41 were diagnosed with NEC. After screening, 2 cases were excluded because of incomplete data. Propensity-matching score (PSM) was performed according to the ratio of 1:2(2 preterm infants in the NEC group were not matched), and finally, 37 cases were in the NEC group (average time to diagnosis was 18.9 days), and 74 cases in the non-NEC group. We compared the difference between the NEC and non-NEC groups in early serum-conjugated bilirubin and total bilirubin levels (time points: the first day of birth, 1 week after birth, 2 weeks after birth). Results (1) The changing trend of conjugated bilirubin was different between the two groups(F = 4.085, P = 0.019). The NEC group's serum-conjugated bilirubin levels gradually increased ( $$\bar x$$  ± s:12.64±2.68; 17.11±4.48; 19.25±11.63), while the non-NEC group did not show a continuous upward trend ( $$\bar x$$  ± s:13.39±2.87; 15.63±3.75; 15.47±4.12). (2) Multiple analyses showed that patent ductus arteriosus(PDA) (odds ratio[OR] = 5.958, 95%confidence interval[CI] = 2.102 ~ 16.882) and increased conjugated bilirubin in the 2nd week (OR = 1.105, 95%CI = 1.013 ~ 1.206) after birth were independent risk factors for NEC. Conclusions The body had already experienced an elevation of conjugated bilirubin before the occurrence of NEC. The change of early conjugated bilirubin may be an important factor in the occurrence of NEC.